Trans-crustal structural control of CO2-rich extensional magmatic systems revealed at Mount Erebus Antarctica - Hill, G J; Wannamaker, P E; Maris, V; Stodt, J A; Kordy, M; Unsworth, M J; Bedrosian, P A; Wallin, E L; Uhlmann, D F; Ogawa, Y; Kyle, P (Nature communications, 2022)
Erebus volcano, Antarctica, with its persistent phonolite lava lake, is a classic example of an evolved, CO2-rich rift volcano. Seismic studies provide limited images of the magmatic system. Here we show using magnetotelluric data that a steep, melt-related conduit of low electrical resistivity originating in the upper mantle undergoes pronounced lateral re-orientation in the deep crust before reaching shallower magmatic storage and the summit lava lake. The lateral turn represents a structural fault-valve controlling episodic flow of magma and CO2 vapour, which replenish and heat the high level phonolite differentiation zone. This magmatic valve lies within an inferred, east-west structural trend forming part of an accommodation zone across the southern termination of the Terror Rift, providing a dilatant magma pathway. Unlike H2O-rich subduction arc volcanoes, CO2-dominated Erebus geophysically shows continuous magmatic structure to shallow crustal depths of < 1 km, as the melt does not experience decompression-related volatile supersaturation and viscous stalling.